Spelling Bee Games: Strategi Meningkatkan Kosakata Bahasa Indonesia - Merlin, Herista; Zulfahita; Yanti, Lili (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This research aims to: 1) Describe the differences in students' mastery of Indonesian vocabulary using the spelling bee method. 2) Determine whether the spelling bee game method is effective in improving students' vocabulary mastery. 3) Examine students' learning activities in class using the spelling bee game method. The population and sample in this study consisted of all fourth-grade students of SDS Karuna Singkawang, totaling 92 students. The data collection techniques used in this study included tests and observations. Data analysis consisted of prerequisite data analysis and final data analysis. Based on the research findings, it was concluded that: 1) There is a significant difference in Indonesian vocabulary mastery between the control and experimental classes, as evidenced by the t-test calculation for two independent samples, where tcalculated (6.69) > ttable (2.00). 2) The spelling bee game method is effective in improving Indonesian vocabulary mastery, as shown by the effect size calculation of 1.12, which falls into the large category. 3) Students' learning activities using the spelling bee game method during lessons reached a percentage of 90%, categorized as very good or active.